2019
DOI: 10.1039/c8bm01519h
|View full text |Cite
|
Sign up to set email alerts
|

A polyethylenimine-based diazeniumdiolate nitric oxide donor accelerates wound healing

Abstract: A polyethylenimine based diazeniumdiolate nitric oxide donor was prepared to accelerate wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…[11] Additionally, therapeutic administration of low molecular weight NO donors may result in accelerated clearance (i.e., rapid diffusion away from the target and concomitant reduced therapeutic activity for cancer, CVD, and bacteria. [7b] To increase the stabilities, and to optimize the pharmacokinetic performance, NONOates [3,66] and SNOs were generally incorporated into various polymeric delivery systems in terms of linear, star, and dendritic polymers, as well as, MOF, mesoporous silica NPs, micelles, and liposomes. [67] Loading NO donors into polymeric delivery systems usually depends on the NO donor properties such as surface charge, hydrophobicity and functional groups.…”
Section: Polymeric No Delivery Nanoplatformsmentioning
confidence: 99%
“…[11] Additionally, therapeutic administration of low molecular weight NO donors may result in accelerated clearance (i.e., rapid diffusion away from the target and concomitant reduced therapeutic activity for cancer, CVD, and bacteria. [7b] To increase the stabilities, and to optimize the pharmacokinetic performance, NONOates [3,66] and SNOs were generally incorporated into various polymeric delivery systems in terms of linear, star, and dendritic polymers, as well as, MOF, mesoporous silica NPs, micelles, and liposomes. [67] Loading NO donors into polymeric delivery systems usually depends on the NO donor properties such as surface charge, hydrophobicity and functional groups.…”
Section: Polymeric No Delivery Nanoplatformsmentioning
confidence: 99%
“…Therefore, NONOate is a kind of very important NO local release compounds. Researchers have developed NONOate macromolecule by developing amine-containing polymeric matrices to control the release of small molecule NONOates effectively (Zhang et al, 2019). These compounds have been widely explored in biomedical fields to show outstanding clinical application prospects.…”
Section: Diazeniumdiolatesmentioning
confidence: 99%
“…In a recent study, propylene oxide was used to functionalized with hyperbranched PEI with the formation of hydroxyl moieties and the residual amine groups was treated with NO. In vivo study on mice revealed that the resulting macromolecular NO donors exhibited accelerated wound healing performance in full thickness excisional cutaneous wound model (Zhang et al, 2019). The PEI-derived NONOate-based NO donors can also be used as the stabilizing agents of inorganic nanoparticles.…”
Section: N-diazeniumdiolate (Nonoate)-based Polymeric No Donorsmentioning
confidence: 99%